2017
DOI: 10.1080/13102818.2017.1282837
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of StAATP, a potato plastidic ATP/ADP transporter gene, increases starch content in transgenic Arabidopsis

Abstract: The plastidic ATP/ADP transporter (AATP) imports adenosine triphosphate (ATP) from the cytosol into plastids, resulting in an increase in the ATP supply to facilitate the anabolic synthesis in heterotrophic plastids of dicotyledonous plants. In this study, a gene encoding the AATP protein, StAATP, was successfully isolated from potato and transformed into Arabidopsis. Constitutive expression of StAATP significantly increased the starch accumulation in the transgenic plants. Realtime quantitative polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…SSS can be grouped into four types, SSS I, SSS II, SSS III and SSS IV [3][4][5]. A large body of evidence has illustrated that up-regulation of these genes could increase starch accumulation in plants [5,[18][19][20][21][31][32][33][34][35]. In our study, a significant increase of SSS activity was also observed in transgenic plants ( Figure 5).…”
Section: Up-regulated Starch Biosynthetic Genes and Increased Enzyme supporting
confidence: 72%
See 1 more Smart Citation
“…SSS can be grouped into four types, SSS I, SSS II, SSS III and SSS IV [3][4][5]. A large body of evidence has illustrated that up-regulation of these genes could increase starch accumulation in plants [5,[18][19][20][21][31][32][33][34][35]. In our study, a significant increase of SSS activity was also observed in transgenic plants ( Figure 5).…”
Section: Up-regulated Starch Biosynthetic Genes and Increased Enzyme supporting
confidence: 72%
“…Heterologous expression of SnRK1 from apple/sweet potato increases the starch content in transgenic tomato/tobacco plants [17,18]. Arabidopsis thaliana plants expressing AATP CONTACT Feibing Wang wangfeibing1986@163.com; wangfeibing@hyit.edu.cn from tomato/potato exhibit higher starch content [19,20]. Overexpression of IbAATP increases the starch and amylose content in transgenic sweet potato [21].…”
Section: Introductionmentioning
confidence: 99%
“…This marker encodes an ATP/ADP transporter gene. Wang et al [43] explained that ATP/ADP transporter genes increase the starch content in transgenic Arabidopsis. This could explain why the kernels of some genotypes became softer under stress conditions.…”
Section: Marker Traits Association For Hardness Under Optimum and Stress Conditionsmentioning
confidence: 99%
“…There a few reports that the AATP gene has been shown to be involved in starch accumulation in plants [17][18][19][20][21][22]. In this work, the VvAATP gene was isolated from grapevine.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of the potato StAATP decreased ADPG level by 25-70% and starch content by 19-51% in potato tubers [18]. Ectopic expression of SlAATP/StAATP/GmAATP from tomato/potato/soybean increased starch accumulation in the leaves of transgenic Arabidopsis plants [19][20][21]. Overexpression of IbAATP increased starch and amylose content in transgenic sweetpotato [22].…”
Section: Introductionmentioning
confidence: 99%